2014
DOI: 10.1111/bjd.13243
|View full text |Cite
|
Sign up to set email alerts
|

‘Memory’ of the stratum corneum: exploration of the epidermis’ past

Abstract: Summary The stratum corneum (SC) is the final product of the process of epidermal differentiation. Besides its crucial protective role as a physical permeability barrier, this composite structure made of cornified keratinocytes embedded in a layered lipid matrix is also, by nature, a tissue that keeps track of past events occurring in the outermost living layers. In normal human epidermis, formation of the SC is very rapid, and during this cornification process several structures expressed by the last granular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…The change in humidity, shape and protein levels is collectively called maturation, ultimately leading to death . During maturation, corneocytes collect intrinsic as well as external influences and can hence be regarded as messengers from inside, representing a kind of skin “memory” …”
Section: How To Avoid a Skin Biopsy?mentioning
confidence: 99%
See 2 more Smart Citations
“…The change in humidity, shape and protein levels is collectively called maturation, ultimately leading to death . During maturation, corneocytes collect intrinsic as well as external influences and can hence be regarded as messengers from inside, representing a kind of skin “memory” …”
Section: How To Avoid a Skin Biopsy?mentioning
confidence: 99%
“…[18] During maturation, corneocytes collect intrinsic as well as external influences and can hence be regarded as messengers from inside, representing a kind of skin "memory". [19]…”
Section: What Can Dead Cells Tell About a Living Organism?mentioning
confidence: 99%
See 1 more Smart Citation
“…Our substudy with lycopene supplementation showed different patterns of lycopene accumulation in desquamated corneocytes and surrounding sebum (Figure ). This difference appears to be easy to explain by the physiological necessity of the transit of terminally differentiated corneocytes through the SC that takes approximately 14 days (Haftek, ). Therefore, desquamation of the first corneocytes enriched with lycopene should start only by the end of the second week of supplementation and is likely to be fully manifested later as we observe (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…The keratinocytes of the epidermis stem from epidermal stem cells which are present in the stratum basale. By dividing they give rise to the transit amplifying cell compartment that ultimately undergoes terminal differentiation and cell death to form the stratum corneum of densely packed cell membranes of keratinocytes (3). Keratinocytes express specific sets of keratins during their passage through the epidermis.…”
Section: The Structure Of the Epidermis Is Linked To The Life Cycle Omentioning
confidence: 99%